ANALISIS KUARTIL, DESIL DAN PERSENTIL PADA UKURAN PANJANG UDANG FLOWER (Penaeus Semisulcatus) DI PERAIRAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Devani Febrianti; Muhammad R. Syahrir; Abdunnur Abdunnur (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
Green Tiger Prawn is one of the Prawn from the Penaeidea family and is one the catches caught in the waters of Samboja. This research conducted in October-December 2021 in the waters of Samboja, Kutai Kartanegara catching prawn at night using trawls. The sample used was 129 green tiger prawn with 90 females and 39 males. This study aims to determine the location of quartiles, deciles and persentiles in prawn data assisted by microsoft Excel software and presented in the form of histogram. The results of this study found that the location of the Q1 quartile was 25%, Q2 was 50% and Q3 was 75%. Decile D1 is 10%, D2 is 20% and D3 is 30%. Percentile P25 is 25%, P50 is 50%, dan P90 is 90%.